A Safety Algorithm of P2P Routing based on Multiple-Encryption Detecting Technology - Chuiwei Lu; Xianhao Miao; Zhiyuan Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The nodes can freely join or leave the P2P network, which will lead to much false routing information that can cripple the performance of P2P network. Many hackers also utilize the weaken point to attack the P2P network. We propose a safety routing algorithm for P2P network to resist the routing attack. The algorithm adopts the multiple-encryption detecting technology. The node which launches the communicating connection will periodically detect every node in its routing path by sending some multiple-encryption detecting packets. By the responding message of the detected nodes, the malicious or disable nodes in its routing path will be accurately located and kicked out of the routing table. Simulation experiments demonstrate the algorithm can effectively improve the safety of the P2P routing and topology stability of the P2P network. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3411